X marks the spot - Soderberg, Erin. (New York : Random House, 2015)
"Wally and his human friend Henry have passed the test. They are now officially Puppy Pirates--and just in time for an exciting new adventure. A treasure hunt! The puppies sail to a deserted island with treasure map in paw, and ready to dig. But uh oh! This island isn't deserted after all..."--
Ages 6-9.
F&P text level: M.
Keywords: Dogs -- Fiction; Pirates -- Fiction; Buried treasure -- Fiction; Adventure and adventurers -- Fiction